2015
DOI: 10.1089/jmf.2014.0084
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Composition and In Vitro Antioxidant Properties of Harungana madagascariensis Stembark Extracts

Abstract: The stembarks of Harungana madagascariensis were analyzed for their content of chemical constituents, antinutrients, vitamin levels, and in vitro antioxidant properties in two solvent systems. Phytochemical screening revealed higher levels of alkaloids, saponins, and flavonoids in the methanolic (MHM) extract than in the dichloromethane (DCM) extract. The methanolic extract had higher contents of minerals, vitamins, and antinutrients except K, vitamin B1, and phytic acid, respectively. Antioxidant potentials o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 31 publications
0
17
1
Order By: Relevance
“…This points to the potential antioxidant and free radical scavenging activity of H. madagascariensis. In previous studies, H. madagascariensis has been described as an antioxidant and free radical scavenger 24,39 . The current study shows the antioxidant activity of H. madagascariensis and endorses its cardioprotective effect mediated by its antioxidant effect in myocardium.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This points to the potential antioxidant and free radical scavenging activity of H. madagascariensis. In previous studies, H. madagascariensis has been described as an antioxidant and free radical scavenger 24,39 . The current study shows the antioxidant activity of H. madagascariensis and endorses its cardioprotective effect mediated by its antioxidant effect in myocardium.…”
Section: Discussionmentioning
confidence: 98%
“…Biological studies on the barks or leaves of this plant revealed antihelminthiase properties 19 , anti-plasmodial 20 , antidiabetic 21 , antimicrobial activities 22 , analgesic and anti-inflammatory activities 23 . Some of the constituents and isolated compounds from H. madagascariensis includes flavonoids, alkaloids, saponins, terpenes, cardiac glycosides, and tannins 24 . A prenylated 1, 4-anthraquinone isolated from the hexane extract of the stem-bark of H. madagascariensis possess alphaglucosidase inhibition and antioxidant activities 25 .…”
Section: Introductionmentioning
confidence: 99%
“…The DPPH test is widely accepted as a tool for assessing antiradical activity of antioxidants. Due to the harmful effects of free radicals on biological membranes, this is extremely important [56]. However, ABTS radical scavenging assay could also be an option when it comes to samples containing hydrophilic, lipophilic, and highly pigmented antioxidant compounds [57].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore [35]. But H. madagascariensis exhibited moderate activity [36] while A. precatorius [37] and B. micrantha [38] have demonstrated effective inhibitions ( Table 1) [39]. However, effective inhibitions were observed on root extracts of D. tripetala (IC 50 0.631 μgmL −1 ) and M. excelsa (IC 50 0.194 μgmL −1 ) compared to 4.60 μgmL −1 ascorbic acid [40].…”
Section: Antioxidant Activities Of Crude Extractsmentioning
confidence: 99%